2001
DOI: 10.1038/35085576
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and transmission of stable CTL escape mutations in HIV infection

Abstract: Increasing evidence indicates that potent anti-HIV-1 activity is mediated by cytotoxic T lymphocytes (CTLs); however, the effects of this immune pressure on viral transmission and evolution have not been determined. Here we investigate mother-child transmission in the setting of human leukocyte antigen (HLA)-B27 expression, selected for analysis because it is associated with prolonged immune containment in adult infection. In adults, mutations in a dominant and highly conserved B27-restricted Gag CTL epitope l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
406
2
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 517 publications
(420 citation statements)
references
References 30 publications
11
406
2
1
Order By: Relevance
“…Under selection pressure from the immune system, HIV-1 also mutates rapidly to evade cytotoxic T lymphocyte responses. These epitopecentric escape mutations typically alter the conformation of exposed residues that interact with the T-cell receptor 50,51,52,53 or abrogate peptide presentation via effects on antigen processing or HLA-I binding 54,55 . Here, we report a novel mode of escape whereby the common T3N mutant exploits the P-1 overhang of TW10 and the anchor residue preferences in the A and B pockets to shift the register of the peptide within HLA-B*57:01.…”
Section: Discussionmentioning
confidence: 99%
“…Under selection pressure from the immune system, HIV-1 also mutates rapidly to evade cytotoxic T lymphocyte responses. These epitopecentric escape mutations typically alter the conformation of exposed residues that interact with the T-cell receptor 50,51,52,53 or abrogate peptide presentation via effects on antigen processing or HLA-I binding 54,55 . Here, we report a novel mode of escape whereby the common T3N mutant exploits the P-1 overhang of TW10 and the anchor residue preferences in the A and B pockets to shift the register of the peptide within HLA-B*57:01.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed HIV has been shown to escape from CTL immune surveillance by mutation at P2 [3,30], and this escape is mediated by immune selection pressure [31,32]. The viral capsid interactions between two neighboring p24 molecules are mediated by residues within the HIV epitope, and it appears that modification of the P6 leucine to methionine permits mutation of the P2 arginine without significant loss of viral fitness [31].…”
Section: Discussionmentioning
confidence: 99%
“…or coincidentally with, mutation of the P2 arginine to threonine, lysine or aspartate [31,32]. Studies have shown that the M6 mutant retains full binding potential to the HLA-B*2705 groove [30,31], and the HLA-B*2705-HIV structure indicates that the P6 leucine side chain, being solvent-exposed, plays little role in stabilizing the HIV epitope's binding to HLA-B*2705.…”
Section: Eur J Immunol 2005 35: 341-351mentioning
confidence: 99%
“…If escape occurs in variable viruses, it is highly epitope dependent, as is clear from detailed studies of HLA-B27-restricted epitopes in HIV [71][72][73]. Some of these epitopes may fall in regions that are 'constrained' or stable within the virus, due to conserved structure or function and multiple 'compensatory' mutations may need to accumulate, which does not occur readily.…”
Section: Success Versus Failure Of T Cell Responses: the Potential Romentioning
confidence: 99%